How Will AI Change Healthcare in Developing Countries? A Dual-Edged Transformation - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2022)
The integration of Artificial Intelligence AI into global healthcare systems represents a paradigm shift, but its impact is perhaps most profound and complex...
Keywords: Digital Health; Diagnostics; Artificial Intelligence; Machine Learning; Medical Ethics